The Effectiveness of Respiratory System Supplement Based on Research for Increasing Motivation and Learning Outcomes in High School - Purwati, Linda; Lisdiana, Lisdiana (Journal of Biology Education, 2020)
A survey of 612 students in one of the high schools in the city of Semarang is found 177 shisha smokers. Based on the results of the survey, students haven’t known the effects and harmful contents of the shisha which they consumed. The use of supplement based on research could increase student knowledge about the dangers of shisha. Manufacture of products based on research data. Learning resources developed are supplement. The appropriateness of product is carried out by the media validator and material validator. Furthermore, the products were tested on 34 students, namely grade XI students of SMA Negeri 1 Kutowinangun. Data collection techniques used questionnaires and written tests. The data analysis method is quantitative descriptive. Based on the results of product validation which it showed very valid. Scores from material experts is 84% ​​and media experts is 98%. The readability test results in the form of teacher and student responses showed incrasing results. The effectiveness of supplement is profed by the scores obtained on motivation scores in before and after learning which increased by 4% with an average percentage in after learning is 77%. Student learning outcomes that have achieved KKM value showed 76,5% and the average N-gain was 0.66 in the medium category. This shows that supplement based on research are effective for increasing motivation and student learning outcomes in high school.